Efficacy and safety of pembrolizumab monotherapy in EGFR-mutant squamous cell lung cancer with PD-L1 over-expression: A case report. Issue 33 (19th August 2022) - Liu, Qiu-Xia; Wei, Jian-Guo; Chen, Yi-Yi; Wang, Jian-Fang
Abstract : Background: Epidermal growth factor receptor (EGFR)-mutant nonsmall cell lung cancer (NSCLC) patients are less likely to be programmed death-ligand 1 (PD-L1)-positive compared with wild-type EGFR mutant tumors. Given the rarity of actionable driver genes in squamous cell lung cancer (SQCC), the frequency of SQCC patients simultaneously carrying EGFR driver gene mutation and having PD-L1 over-expression is extremely low. Studies on the effectiveness and safety of EGFR-TKIs or immune-checkpoint inhibitors (ICIs) in this subset of patients are lacking. Patient concerns: The patient suffered from coughing and chest pain for 1 month. A chest CT revealed a mass with a cavity in the right lung, enlarged mediastinal lymph nodes, diffuse pleural thickening in the right pleura, and pleural effusion of the right chest. Diagnosis: A pleural biopsy was performed using a video-assisted thoracoscope. The pathological examination revealed a poorly differentiated squamous cell carcinoma of lung. Further genetic testing identified exon 19 deletion mutation in EGFR with abundance of 0.27%. Meanwhile, immunohistochemical PD-L1 analysis showed a TPS of 90%. Interventions: The patient was initially resistant to EGFR-TKIs but exhibited a rapid and marked response to pembrolizumab. Outcomes: After 5 cycles of pembrolizumab monotherapy, the patient developed Grade 3 immune-related dermatitis, and ICI therapy was suspended. Conclusions: ICI monotherapy could be an effective therapy in SQCC patients with low-abundance of EGFR mutations and PD-L1 over-expression. However, close attention should be paid to immune-related adverse events.